2022
DOI: 10.4102/sajp.v78i1.1764
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nonpharmacological therapeutic interventions on pain and physical function in adults with rib fractures during acute care: A systematic review and meta-analysis

Abstract: Background: Rib fractures are a common thoracic injury and notable source of chest pain. Chest pain may lead to compromised respiratory and physical function.Objectives: Our study aimed to synthesise the evidence on the effectiveness of nonpharmacological therapeutic interventions on pain and physical function in adults admitted with rib fractures to acute care settings. Secondary outcomes included length of stay (LOS), respiratory complications, respiratory function and mortality rate.Method: A systematic lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…43 A systematic review showed acupuncture, transcutaneous electrical nerve stimulation (TENS), noninvasive ventilation (NIV) modalities, physiotherapy techniques, and multidisciplinary pathways used alongside pharmacological interventions are effective for use in the treatment of acute rib fractures. 44 Grammatopoulou et al investigated the effect of the active cycle of breathing technique (ACBT), added to standard physiotherapy management (body positioning, IS, supported coughing, and early mobilization), and analgesia administration on pain levels in adult patients with three or more rib fractures. This reduced pain on days 3-7 of hospitalization.…”
Section: Multidisciplinary Approachmentioning
confidence: 99%
“…43 A systematic review showed acupuncture, transcutaneous electrical nerve stimulation (TENS), noninvasive ventilation (NIV) modalities, physiotherapy techniques, and multidisciplinary pathways used alongside pharmacological interventions are effective for use in the treatment of acute rib fractures. 44 Grammatopoulou et al investigated the effect of the active cycle of breathing technique (ACBT), added to standard physiotherapy management (body positioning, IS, supported coughing, and early mobilization), and analgesia administration on pain levels in adult patients with three or more rib fractures. This reduced pain on days 3-7 of hospitalization.…”
Section: Multidisciplinary Approachmentioning
confidence: 99%